Literature and human rights : the law, the language and the limitations of human rights discourse - Ward, Ian, 1963- (Law & literature (De Gruyter), 2015)
The idea of human rights is not new. But the importance of taking rights seriously has never been more urgent. The eighteen essays which comprise Literature and Human Rights are written as a contribution to this vital debate. Each moreover is written in the spirit of interdisciplinarity, reaching across the myriad constitutive disciplines of law, literature and the humanities in order to present an array of alternative perspectives on the nature and meaning of human rights in the modern world. The taking of human rights seriously, it will be suggested, depends just as much on taking seriously the idea of the human as it does the idea of rights.